2022
DOI: 10.2147/opth.s352964
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Toward Self-Medicating Eye Symptoms in Saudi Arabia

Abstract: Purpose Self-medication is the selection and use of drugs by individuals to treat self-diagnosed diseases or symptoms. While some patients regard self-medicating as harmless, it is far from being a safe practice. The aim of this study was to evaluate the knowledge, attitudes, and practices toward self-medicating eye symptoms in Saudi Arabia. Patients and Methods A cross-sectional study was conducted through an online questionnaire on a study population that consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Other major reasons for self-medication include financial constraints, desire for quick relief, experience from previous ocular illness, advice from family and friends, and poor knowledge of the hazards of self-medication. 13 In a study conducted by Adimassu et al 9 in Northeast Ethiopia, absence of health insurance was associated with a fourfold risk for the practice of self-medication. In Ghana, Kyei et al 10 documented similar findings, as they reported a significant association between self-medication and health insurance with noninsured persons being more likely to self-medicate than persons with health insurance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other major reasons for self-medication include financial constraints, desire for quick relief, experience from previous ocular illness, advice from family and friends, and poor knowledge of the hazards of self-medication. 13 In a study conducted by Adimassu et al 9 in Northeast Ethiopia, absence of health insurance was associated with a fourfold risk for the practice of self-medication. In Ghana, Kyei et al 10 documented similar findings, as they reported a significant association between self-medication and health insurance with noninsured persons being more likely to self-medicate than persons with health insurance.…”
Section: Discussionmentioning
confidence: 96%
“…Other major reasons for self-medication include financial constraints, desire for quick relief, experience from previous ocular illness, advice from family and friends, and poor knowledge of the hazards of self-medication 13 . In a study conducted by Adimassu et al 9 in Northeast Ethiopia, absence of health insurance was associated with a fourfold risk for the practice of self-medication.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was obtained from previously published research with similar aims [12]. An online self-administered questionnaire was developed, facevalidated, and pretested to align with the study objectives.…”
Section: Data Collection Management and Statistical Analysismentioning
confidence: 99%
“…In 2021, a cross-sectional study conducted in the Riyadh region aimed to investigate the patterns of SM in ophthalmology. The results of the study exhibited a high prevalence (37.2%) of SM [12]. Moreover, in 2020, in Taif City, a cross-sectional study assessed the prevalence of SM and attitude and practice regarding the use of Traditional Eye Medicine (TEM) for eye-related problems.…”
Section: Introductionmentioning
confidence: 99%
“…Although over-the-counter (OTC) drugs are meant for self-medication and are of proven efficacy and safety, their improper use due to a lack of knowledge of their side effects and interactions could have serious implications, especially in extremes of ages (children and old age) and special physiological conditions, such as pregnancy and lactation [ 8 ]. Self-medication practice is a common phenomenon all over the world, including in industrialized and developing countries [ 9 - 10 ]. The prevalence of irresponsible self-medication is high all over the world [ 11 ].…”
Section: Introductionmentioning
confidence: 99%